Mental Health Characteristics of the Elderly in Tegal City - Khotimah, Khusnul; Trisnawati, Yuli; Heriyono, Muhamad; Vianadin, Adinda Putri (Jurnal Kesmas Prima Indonesia, 2025)
The number of elderly people in Indonesia is estimated to increase to 27.08 million in 2020 and will continue to increase to 48.19 million in 2030 and will become 48.19 million in 2040.year2035. Many studies have shown that mental health is the most important factor affecting the lives of the elderly. To find out the factors related to mental health in the elderly in Panggung Village, Tegal Timur District, Tegal City. The instrument used in this study is the WHOQOL-BREF (World Health Organization Quality Of Life-BREF) quality of life instrument which is a development of the WHOQOL-100 instrument. The analysis used the chi square test with a significance level of 95%. Based on the results of this study, it was found that there was no relationship between gender, education, occupation, socio-economics with mental health in the elderly and there was a relationship between physical and environmental conditions with mental health in the elderly.